Pengembangan Energi Terbarukan dalam Upaya Mewujudkan Pembangunan Berkelanjutan di PT. Pertamina - Carel Anthony Filemon Patra (Jurnal Green Growth dan Manajemen Lingkungan, 2022)
The purpose of this paper is to provide an explanation of facts about efforts to develop new and renewable energy at PT. PERTAMINA in an effort to realize sustainable development. The method used in this study uses descriptive qualitative methods using data from the Sustainability Report of PT. PERTAMINA in 2021 with a focus on data collection on the new and renewable energy development sector. The results of the study obtained that broadly PT. PERTAMINA seeks to develop new and renewable energy in an effort to realize sustainable development by collaborating with various companies from within the country and abroad with the aim of accelerating the development of new and renewable energy, but there are still obstacles in its development starting in terms of inadequate human resources and also inadequate technology for the process of innovation and research on the development of new and renewable energy. Equity and community participation under the auspices of PT. PERTAMINA needs to be added in an effort to educate the public on the importance of using new and renewable energy.